2.Synthesis, crystal structure and magnetic properties of the mixed-ligand complex [Gd(F3CCO2)3(phen)2(H2O)] - Rizzi, Alberto Claudio; Baggio, Ricardo Fortunato; Calvo, Rafael; Garland, Marías; Peña, Octavio; Perec, Mireille (American Chemical Society, 2001)
Fil: Rizzi, Alberto Claudio. Universidad Nacional del Litoral. Facultad de Bioquímica y Ciencias Biológicas. Departamento de Física; Argentina